Formy komunikacji wykorzystywane w porozumiewaniu się osób głuchoniewidomych - Jakoniuk-Diallo , Anna (Studia Edukacyjne, 2020)
Deafblindness is a disability resulting from simultaneous damage to the two major senses of hearing and sight. It causes limitations in various areas of life, e.g. making contact with other people difficult. The source of communication barriers with deaf people are both cognitive deficits and the different ways of communicating, such as sign language in the palm of the hand, Makaton, Lorm alphabet, etc.